Managing A Case Of Acute Respiratory Distress By A Paramedic (The Review of Diabetic Studies, 2025)
Acute respiratory distress represents a critical medical emergency characterized by rapid onset of difficulty breathing and inadequate oxygenation due to lung dysfunction. Paramedics serve as the first clinical point of contact and are uniquely positioned to perform critical assessments, initiate oxygenation and ventilation support, and rapidly triage patients. Approximately 12% of non-traumatic, non-cardiac arrest EMS encounters involve respiratory distress, with increasing incidence among elderly populations and those with chronic comorbidities. Paramedics face challenges in evaluating acute respiratory distress due to limited diagnostic tools, patient history constraints, uncontrolled environments, multiple comorbidities, and urgency of care. The assessment process follows systematic principles to rapidly identify life-threatening conditions, prioritizing airway, breathing, and circulation. Paramedics perform critical interventions focused on airway management, oxygen therapy, ventilatory support, pharmacological therapies, and circulatory support. Continuous pulse oximetry and capnography enable monitoring of oxygenation and ventilation status. Pediatric patients present unique challenges due to distinct anatomical and physiological features. Geriatric patients with comorbidities may present atypically and are at higher risk for complications and mortality. Pregnant patients require prioritization of maternal stabilization and fetal monitoring. Trauma-related acute respiratory distress arises from direct airway compromise, pulmonary injury, or neurological impairment. Prehospital management is constrained by limited diagnostics, environmental factors, narrow intervention windows, and variability in paramedic training and equipment. Leading EMS guidelines emphasize early oxygenation support, non-invasive ventilation, and advanced airway management when necessary. Future directions include advances in portable respiratory monitoring, point-of-care lung ultrasound, AI-assisted triage and intervention protocols, and expanded scope for paramedics in critical respiratory cases.